Effects of MV PILC Cables Ageing Process on the Diagnostic Parameters: p-factor and tanδ - Mladenovic, Ivana; Weindl, Christian; Scharrer, Thomas (11th IEEE International Conference on Solid Dielectrics, 2013)
During field operation, power equipment is exposed to numerous impacts (especially thermal and electrical stress), which result in a continuous deterioration of its insulation material. The grade of the deterioration can be weighted by different diagnostic measurements. Within an accelerated ageing experiment on paper insulated lead covered (PILC) cables, several diagnostic parameters have been measured regularly during the ageing process of ca. 2 years. The cable samples are PILC cables (20 kV, 150 mm2) of 13 m length, which are differently pre-aged (from brand new, up to cables that have been in operation for 60 years). In this article aging effects of this insulation system on dissipation factor and parameters of return voltage curve as well as on p-factor will be shown and discusse
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.leen.effect
Keywords: medium voltage cable; PILC cable; diagnostics; ageing; dissipation factor; return voltage